Structural characteristics of Brassica rapa L. Polysaccharide and its bioactivity on alcoholic liver injury - Xin Xu; Xinxin Yang; Meng Wang; Jingrong Zhu; Jing Li; Caiyue Chen; Jiameng Liu; Jiahuan Zheng; Bei Fan; Fengzhong Wang; Jing Sun (Ultrasonics Sonochemistry)
The global prevalence of alcoholic liver disease (ALD) has shown a concerning upward trend, with an increasing incidence among younger demographics. In this study, ultrasound-assisted extraction was employed to isolate polysaccharides from Brassica rapa L (BRL). The purified polysaccharide (BRLPP) was structurally characterized, and its protective effects against alcoholic liver disease (ALD) were investigated. The optimal conditions, material-to-liquid ratio of 1:30 and 200 W ultrasonication for 3 h, yielded 6.90 % ± 0.39 % BRLP. Subsequent structural analysis revealed that BRLPP had an average molecular weight of 5.72 × 104 Da and was primarily composed of glucose and arabinose in a molar ratio of 94.29:3.06. GC–MS analysis further identified three major glycosidic linkage patterns: →4)-Glcp-(1→, →4,6)-Glcp-(1→, and → 3,4)-Glcp-(1 → . Strong antioxidant activity was displayed by BRLPP, which showed notable scavenging effects on DPPH and ABTS+ radicals. Using 2 % ethanol exposure, a zebrafish ALD model was created to assess its hepatoprotective potential. The results indicated that BRLPP effectively attenuated ethanol-induced liver damage by reducing serum ALT (Alanine aminotransferase) and AST (Aspartate transaminase) levels. Additionally, BRLPP mitigated oxidative stress by modulating the activities of key biomarkers, including SOD (Superoxide dismutase), MDA (Malondialdehyde), and GSH-Px (Glutathione peroxidase). These results point to BRLPP’s potential as a bioactive component in functional foods for the prevention and treatment of ALD by indicating that it has noteworthy hepatoprotective and antioxidant qualities.